Managing marine disease emergencies in an era of rapid change - Groner, Maya L; Maynard, Jeffrey; Breyta, Rachel; Carnegie, Ryan B; Dobson, Andy; Friedman, Carolyn S; Froelich, Brett; Garren, Melissa; Gulland, Frances M D; Heron, Scott F; Noble, Rachel T; Revie, Crawford W; et al. (Philosophical transactions of the Royal Society of London. Series B. Biological sciences, 2016)
Infectious marine diseases can decimate populations and are increasing among some taxa due to global change and our increasing reliance on marine environments. Marine diseases become emergencies when significant ecological, economic or social impacts occur. We can prepare for and manage these emergencies through improved surveillance, and the development and iterative refinement of approaches to mitigate disease and its impacts. Improving surveillance requires fast, accurate diagnoses, forecasting disease risk and real-time monitoring of disease-promoting environmental conditions. Diversifying impact mitigation involves increasing host resilience to disease, reducing pathogen abundance and managing environmental factors that facilitate disease. Disease surveillance and mitigation can be adaptive if informed by research advances and catalysed by communication among observers, researchers and decision-makers using information-sharing platforms. Recent increases in the awareness of the threats posed by marine diseases may lead to policy frameworks that facilitate the responses and management that marine disease emergencies require.